"More Symbolic—More Political—Than Substantive": An Interview with James R. Clapper on the U.S. Designation of Foreign Terrorist Organizations. Issue 2 (4th March 2018) - Legrand, Tim
ABSTRACT: This article considers the status and value of the U.S. Designated Foreign Terrorist Organizations (FTO) list via an extended and annotated interview with James R. Clapper, U.S. Director of National Intelligence during the administration of President Barack Obama from 2010–2017. In this interview, 1 Clapper reflects on the role and effectiveness of blacklisting for U.S. national security strategy. The article frames the interview within debates in recent political science and law literatures on blacklisting to situate Clapper's views. Drawing on recent controversies—including the fraught relationship between the U.S., Pakistan, the Taliban regime, and the Haqqani network—Clapper speaks to the a) symbolism and foreign policy drivers of FTO listing; b) implications of the FTO list for peace negotiations; and, c) the cohesion of terrorist groups and the effectiveness of FTO listings. In reporting the interview thus, the article offers a rare direct insight to the causal reasoning of an elite security official with respect to a process that has, since its inception in 1997, been shrouded in ambiguity and controversy.